Sarawak Malay language in poem - Juki, Hamsiah (Human Resource Management Academic Research Society, 2017)
This study discusses one of the art forms in the Sarawak Malay society namely the Language in the Sarawak Malay Poem in the linguistic perspective. The aspect focused on, is the language found in the Sarawak Malay poem. The results of observations of the material found that the poem created or uttered spontaneously and naturally it is useful as a means to entertain, educate and to criticize societal behaviour. By their very nature, poems are entertainment and leisure. Based on analysis of the material, submissions made in the objectives of the study was to study the artistic language of the Sarawak Malay poem, identify the poem as materials related to language, literature and culture of the traditional Malays in the state of Sarawak, identify the language contents from the angle of beauty of form, the structure of the poetic Malay Sarawak poem and explain the content, flow, attitude, characteristic and philosophy in Sarawak Malay poem. An analysis was also conducted on assumption of the community on poems through 27 ethnic groups in Sarawak who have languages, way of life and different cultures. Settlements on the coast comprising of Malays and Melanau. Settlements in the river valley comptising of the Iban, Bidayuh and Kenyah. Settlements in the interior comprising of the Kelabit, Penan and Murut. Pattern of settlements and scattered communities which are dispersed cause the Sarawak communities to be in less contact with outsiders and, thus forming a distinctive respective cultural identities depending on the environment. It is to be noted that in the fields of culture and art, especially that involves language, literature and culture undergo changes from time to time. Traditional poems that accompany most traditional cultural presentations such as Sarawak poetry, folk songs, games, dances, religious ceremonies and ritual rites and customs are increasingly marginalized in public conversations.